2021
DOI: 10.2147/idr.s331957
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Hepatic Echinococcosis and the Characteristic CT and MRI Imaging Manifestations

Abstract: Hepatic echinococcosis is a parasitic, infectious disease with a high incidence in pastoral areas. It is highly infectious with a poor prognosis in some cases, which seriously affects the quality of life for people living in pastoral areas. This study aims to discuss the radiological characteristics, including computed tomography (CT) and magnetic resonance imaging (MRI), of hepatic echinococcosis from its definition, transmission, and pathological physiology. The characteristics of CT and MRI manifestations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Kodama et al reported the MRI presentation and characteristics of 35 cases of HAE and classified them into 5 types: type I is multiple small vesicles without a solid mass; type II is multiple small vesicles with a solid mass; type III is a solid component surrounding a large and/or irregular cyst with multiple small vesicles; type IV is a solid mass without small vesicles; type V is a large vesicle without a solid mass; the lesion is predominantly low signal on both T1WI/T2WI, with small vesicles showing a high signal on T2WI and mildly enhancing at the edges of the lesion after enhancement ( 8 ). Yu et al reported that the basic CT signs of HAE include a heterogeneous and substantial mass with unremarkable enhancement on enhanced scans; characteristic features include vesicular signs, calcified foci, central liquefied necrosis or cavities ( 9 ). The imaging presentation of this case was consistent with HAE type III, as proposed by Kodama et al Small cysts could be seen within the solid component.…”
Section: Discussionmentioning
confidence: 99%
“…Kodama et al reported the MRI presentation and characteristics of 35 cases of HAE and classified them into 5 types: type I is multiple small vesicles without a solid mass; type II is multiple small vesicles with a solid mass; type III is a solid component surrounding a large and/or irregular cyst with multiple small vesicles; type IV is a solid mass without small vesicles; type V is a large vesicle without a solid mass; the lesion is predominantly low signal on both T1WI/T2WI, with small vesicles showing a high signal on T2WI and mildly enhancing at the edges of the lesion after enhancement ( 8 ). Yu et al reported that the basic CT signs of HAE include a heterogeneous and substantial mass with unremarkable enhancement on enhanced scans; characteristic features include vesicular signs, calcified foci, central liquefied necrosis or cavities ( 9 ). The imaging presentation of this case was consistent with HAE type III, as proposed by Kodama et al Small cysts could be seen within the solid component.…”
Section: Discussionmentioning
confidence: 99%
“…The location of the focus and its relationship with blood vessels and biliary tracts can be displayed in many directions, which can more accurately assess vascular and biliary complications. It is extremely important for selecting treatment plans, designing operation modes and predicting surgical risk [ 7 , 28 , 29 ]. Since Kodama et al [ 30 ] classified AE into five subtypes by MRI, it is suggested that the characteristics of AE lesions in CEUS may depend on the subtype of AE.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic CT or T2-weighted MRI findings of liver AE are mainly multiple, indistinct and irregular low-density lesions ( 3 , 14 ). Extrahepatic lesions have a multicystic, honeycomb appearance, with septations, and may be accompanied by calcification and/or rim enhancement ( 3 , 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%